2020
DOI: 10.3389/fpsyg.2020.01503
|View full text |Cite
|
Sign up to set email alerts
|

Prompting Children’s Belief Revision About Balance Through Primary and Secondary Sources of Evidence

Abstract: Prior evidence has shown that children's understanding of balance proceeds through stages. Children go from a stage where they lack a consistent theory (No Theory), to becoming Center Theorists at around age 6 (believing that all objects balance in their geometric center), to Mass Theorists at around age 8, when they begin to consider the distribution of objects' mass. In this study we adapted prior testing paradigms to examine 5-year-olds' understanding of balance and compared children's learning about balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…The current research extends this prior work by focusing on a sample of young children, whose theories may be more flexible and thus more responsive to anomalies compared to the samples used in prior research. We also build on recent research that has demonstrated the beneficial effect of rich conceptual explanations for young children’s learning of new scientific knowledge, as shown by their improved scientific understanding when exposed to viable theories about concepts in the domain of biology (Ganea, Ma, & Deloache, 2011; Kelemen, Emmons, Seston Schillaci, & Ganea, 2014; Strouse & Ganea, 2016; Larsen, Venkadasalam, & Ganea, 2020; Venkadasalam & Ganea, 2018). We extend on this prior work by examining the effect of conceptual explanations (which provide an alternative viable theory to children’s naive theory) on children’s ability to capitalize on the observation of anomalous evidence, and their combined effect on children’s scientific belief revision.…”
mentioning
confidence: 99%
“…The current research extends this prior work by focusing on a sample of young children, whose theories may be more flexible and thus more responsive to anomalies compared to the samples used in prior research. We also build on recent research that has demonstrated the beneficial effect of rich conceptual explanations for young children’s learning of new scientific knowledge, as shown by their improved scientific understanding when exposed to viable theories about concepts in the domain of biology (Ganea, Ma, & Deloache, 2011; Kelemen, Emmons, Seston Schillaci, & Ganea, 2014; Strouse & Ganea, 2016; Larsen, Venkadasalam, & Ganea, 2020; Venkadasalam & Ganea, 2018). We extend on this prior work by examining the effect of conceptual explanations (which provide an alternative viable theory to children’s naive theory) on children’s ability to capitalize on the observation of anomalous evidence, and their combined effect on children’s scientific belief revision.…”
mentioning
confidence: 99%
“…This research adds to a body of literature showing that explanations can facilitate conceptual change (Ganea et al, 2021; Kelemen et al, 2014; Kendeou et al, 2014; Larsen et al, 2020; Tippett, 2010; Venkadasalam & Ganea, 2018). In Experiment 2, children who learned that gravity affects the rate at which objects fall were better able to generalize and retain this understanding than children who did not hear an explanation.…”
Section: Discussionmentioning
confidence: 70%
“…One study examined the impact of explanations combined with anomalous evidence embedded in guided activities that children experienced first-hand compared to picture books they listened to (Larsen et al, 2020). Five-year-olds learned to balance asymmetrical objects equally well from both interventions compared to a baseline activity with no guidance and a control book about plants.…”
Section: Intuitive Theories Conceptual Change and Anomalous Evidencementioning
confidence: 99%
“…Primary data is data that is taken directly through direct observation or experimentation from the object of research. While secondary data is obtained by explaining primary source evidence through various media such as books, scientific journals/articles, websites, or verbal evidence (Larsen et al, 2020). Observation of the main parameters in the form of gonadal sampling was carried out 3 times during the study for 15 days.…”
Section: Methodsmentioning
confidence: 99%